Pellet diameter and morphology of European Ganoderma pfeifferi in a repeated-batch fermentation for exopolysaccharide production - Supramani, Sugenendran; Jailani, Nurulhuda; Ramarao, Kivaandra; Mohd Zain, Nurul Amalina; Klaus, Anita; Ahmad, Rahayu; Wan-Mohtar, Wan Abd Al Qadr Imad (Elsevier, 2019)
The pellet diameter and morphology of an underutilized European Ganoderma pfeifferi (EGP) mycelium was studied in a repeated-batch fermentation (RBF) for exopolysaccharide (EPS) production. In preliminary fermentation, growth screening was performed for initial pH, glucose concentration, and agitation speed. At 30 °C, the favourable conditions for EPS production (0.58 g/L) and EPS productivity (0.058 g/L day −1 ) were 15 g/L glucose, initial pH 6, and 100 rpm, while the highest dry cell weight (DCW; 3.63 g/L) was achieved at 9 g/L glucose, initial pH 4, and 120 rpm. Morphologically verified, large, compact pellets (diameter: 40 μm < d < 40.67 μm) were associated with high DCW while small dispersed pellets (diameter: 11.67 μm < d < 14.67 μm) were associated with high EPS production. In RBF, EGP mycelium exhibited the ability to self-immobilize and high stability for repeated use with increasing smooth pellet diameter from RBF1 (7.33 μm < d < 7.67 μm) to RBF4 (16.67 μm < d < 18.33 μm). The fermentation period was subsequently shortened from 48 (batch) to 24 days in four consecutive cycles of RBF, and the productivity of EPS increased from 0.053 g/L day −1 to 0.108 g/L day −1 . In an FTIR analysis, crude EPS of EGP showed the presence of β-glucan characteristics at 1075 cm −1 and 891 cm −1 wavelengths, similar with European G. lucidum BCCM 31549. In addition, 1 H NMR showed similar β-glycosidic linkages when compared with laminarin standard. The proposed strategy demonstrated that G. pfeifferi pellet morphology can withstand extended fermentation cycles for efficient EPS production. © 2019 Elsevier Ltd